Computer-based methodologies for semi-automatic 3D model generation from paintings. (1st January 2014) - Volpe, Y.; Furferi, R.; Governi, L.; Tennirelli, G.
Over the last few years, technologies like 3D scanning and rapid prototyping provided an extraordinary boost in improving reproductions of 3D artworks, like sculptures and historical buildings, all over the world. Physical 3D reproduction of subjects represented in paintings, is recognised to be one of the best ways to allow visually impaired people to enjoy such kind of artworks. However, the use of advanced technologies with the aim of realising 3D models starting from paintings has not been satisfactorily investigated yet. Though a number of algorithms coming from computer vision science exist to cope with similar issues, the specific problem of producing a 3D representation which is targeted at blind people tactile exploration has been only marginally investigated. Starting from these considerations, this work presents 1) a quite extensive review of the criteria proposed in literature for producing tactile models suitable for blind people and 2) four alternative computer-based methods for semi-automatic generation of tactile 3D models starting from RGB digital images of paintings. The outcomes of this study contribute new information to the field of visually impaired user-oriented 3D reconstruction and clearly indicate the strategy to be adopted in order to produce a meaningful reproduction of a bi-dimensional piece of artwork.